The oretical and practical issues of consumer protection (Journal of actual problems of jurisprudence, 2018)
The article deals with consumer protection issues and the history of the emergence of consumer rights protection in the United States. And also discussed the formation of the rule of law for the protection of rights and legal interests of consumers in all civil and legal relations in the Republic of Kazakhstan.Key words: Constitution, the Convention, the consumer, rights, interests, sovereignty, law.